Simulation of the soil water content under different water deficits for apple trees via improved WOFOST-HYDRUS coupled model - Zhao, Long; Zhang, Haoran; Zhao, Xinbo; Ding, Yuehua; Shi, Yi; Cui, Ningbo; Qiu, Zhaomei (International Journal of Agricultural and Biological Engineering, 2025)
As a crucial fruit tree crop, the health and yield of apple trees are intricately linked to soil moisture conditions. This study aimed to integrate the enhanced WOFOST model with the HYDRUS model to simulate the growth and development of apple trees, as well as the dynamics of soil moisture under varying degrees of water deficit. The outputs of evapotranspiration (ET0) and leaf area index (LAI) from the WOFOST model during the apple growth phase were specifically integrated with HYDRUS-1D. These parameters served as intermediaries to assess the impact of different water deficit scenarios on apple tree growth and soil moisture content. The experimental design included three levels of water deficit treatments in addition to control, with irrigation volumes for the deficit treatments set at 85%, 70%, and 55% of the control’s volume, respectively. The model-predicted LAI across all irrigation treatments exhibited an R2 range of 0.89-0.95, a normalized root mean square error (NRMSE) between 8.02% and 14.57%, and yield prediction errors ranging from 6.27% to 9.61%, closely aligned with empirical data. The accuracy of simulated soil moisture content was enhanced in the 0-30 cm layer, with a slight decrease in accuracy observed in the 30-60 cm layer. For each irrigation treatment, the R2 values for simulated soil moisture content ranged from 0.77 to 0.89 in the 0-30 cm layer and from 0.75 to 0.81 in the 30-60 cm layer. This study validated the capability of the WOFOST-HYDRUS model to accurately simulate the effects of varied water deficit treatments on soil moisture, LAI, and apple tree yield, providing valuable insights for developing optimal irrigation strategies. Keywords: growth model, WOFOST-HYDRUS, apple trees, water simulation, water deficit treatment DOI: 10.25165/j.ijabe.20251801.9384 Citation: Zhao L, Zhang H R, Zhao X B, Ding Y H, Shi Y, Cui N B, et al. Simulation of the soil water content under different water deficits for apple trees via improved WOFOST-HYDRUS coupled model. Int J Agric & Biol Eng, 2025; 18(1): 219–229.